Maintaining and revitalising Balinese language in public space: A controversial language planning regulation. Issue 145 (2nd September 2021) - Mulyawan, I Wayan
ABSTRACT: Kuta in Bali, is an over developed urban city, observed through the emergence of outdoor signs along the main streets. However, there were no local laws to regulate the use of local language in public spaces, which led to the marginalisation of the Balinese language. In 2018, Bali's Governor Regulation no. 80/2018 was issued to regulate the use of languages in Bali, exclusively to maintain local language in public spaces. This study is aimed at investigating the effect of the regulation on the use of local language in Kuta's public spaces. The data were collected from six main streets in Kuta in January 2020. The result showed that the Balinese language had gained a prestigious position in public space with its addition on many outdoor signages. Conversely, this regulation is alleged to violate national law that obliges all public signs be in the Indonesian language and placed above local and or foreign languages on the same sign board.